Endometrioid Adenocarcinoma Arising in a Paratubal Cyst: A Case Report and Review of the Literature. Issue 3 (March 2017) - Chang, Catherine; Matsuo, Koji; Mhawech-Fauceglia, Paulette
Abstract : A 56-year-old G3P3 postmenopausal woman presented with a 5 month history of abnormal uterine bleeding and pelvic pain. A computed tomographic scan revealed a 5 cm right adnexal cystic mass in addition to a thickened, heterogenous endometrium and leiomyomatous uterus. A total laparascopic hysterectomy and bilateral salpingo-oophorectomy with omental and peritoneal biopsy were performed. Gross examination revealed a 12 week size uterus with small fibroids, normal bilateral atrophic ovaries, and a right paratubal cyst. A 4 cm vegetating mass was found in the right side of the uterine wall. Microscopically, the uterine mass was diagnosed as an endometrioid adenocarcinoma (EAC) FIGO 1 with 70% of myometrial invasion. The remaining endometrium showed a complex atypical hyperplasia. In addition, a 5 cm paratubal cystic mass was found that was separate from the uterus and the right adnexa. The cyst content was a chocolate brown fluid and the cyst wall was smooth with a single solid mass of 2 cm in size. The diagnosis of EAC, FIGO 1 was given. The remaining cyst lining showed endometriotic cyst and foci of endometriosis in the cyst wall. There was no lymphovascular invasion. The entire fallopian tube and ovaries were submitted and they were free of tumor. The patient was diagnosed with primary EAC of the paratubal cyst in addition to EAC of the uterine corpus (pT1b). A close follow-up was recommended. Because of our limited knowledge of carcinomas arising in the paratubal cyst, we will review the literature and discuss their clinical aspects, management, and behavior.